Emergence and transmission of misinformation in the context of social interactions - Saraiva, Magda (2020)
The emergence and transmission of false memories is well documented in individual memory tasks. However, the examination of these processes in the context of social interaction still presents mixed findings. The present study further examines the potential of collaboration in minimizing the acceptance and retrieval of misinformation. In Experiment1participants watched a video immediately followed by a recall task (collaborative vs. nominal). Then a questionnaire (collaborative vs. individual) containing true information and misinformation about the video was presented. After the questionnaire, participants were given a new recall task (collaborative vs. nominal). We expected that collaboration at encoding and at retrieval would reduce the acceptance and recall of misinformation. Results revealed, as expected, that collaborative groups performed better in answering the questionnaire, accepting more correct information and rejecting more misinformation. Subsequently, they also recalled less misinformation. However, their recall of correct information was also lower. To rule out the potential role of collaborative inhibition in explaining the results observed in the final recall, in Experiment2the collaborative manipulation occurred only during the questionnaire and both recall tasks were individual. Again, participants answering the questionnaire collaboratively performed better than those answering individually. Critically, in a subsequent individual recall task, they produced less false memories and more correct information than those answering the questionnaire individually. These results suggest that collaboration during information encoding reduces the acceptance of misinformation and its subsequent recall.